2020
DOI: 10.33899/ijvs.2019.126172.1255
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of Jaagsiekte sheep retrovirus (JSRV) in Iraqi Awassi sheep

Abstract: Jaagsiekte sheep retrovirus (JSRV) infection in sheep results in contagious ovine pulmonary adenocarcinoma (OPA). The aim of this study was to detect the presence of JSRV in Iraqi Awassi sheep of Al-Qadisiyah Province using reverse transcription-PCR (RT-PCR). Lung secretion samples from 50 adult sheep (1.5 to 2-year-old) during 2016-2018 that were suffering from chronic respiratory distress with suspected clinical OPA were collected. RT-PCR assay for detection of JSRV was conducted using primers specific for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…The study also revealed that the molecular technique is an accurate and sensitive method for detection and identification of the causative pathogen. This finding is consistent with what mention in literature of (46,47).…”
Section: Discussionsupporting
confidence: 94%
“…The study also revealed that the molecular technique is an accurate and sensitive method for detection and identification of the causative pathogen. This finding is consistent with what mention in literature of (46,47).…”
Section: Discussionsupporting
confidence: 94%
“…Sixty mature third instars were chosen and reared in plastic vials containing sand and a bovine meat portion and marked individually (11,12). The pots were covered with gauze in room temperature at average of 23ºC and average humidity 44.3.…”
Section: Methodsmentioning
confidence: 99%
“…The disease OPA has been studied in different countries of the world, involving Iraq [3][4][5]9]. The occurrence of disease throughout the world is either sporadic or endemic and it is characterized as important disease of sheep and goats [11].…”
Section: Discussionmentioning
confidence: 99%
“…The diseases resulting from an infection of a virus belonging to a beta retrovirus called Jaagsiekte sheep retrovirus (JSRV) [1]. OPA was first recorded in South Africa in the 19th century where it was called Jaagsiekte which is derived from the Afrikaans for (chasing sicknesses) and disease has been noticed in wide types of breeds of sheep and in different countries over the world [2][3][4][5]. The characteristic of tumor cells in OPA thought to be originated from type two of alveolar epithelial cells or Clara cells, which is recorded as secretary cells and lining the epithelium of alveoli of the lung therefore, the disease is characterized by excessive secretion fluids by the tumor cells and these fluids are accumulated in the lung, which be sources of infectious virus and causes important economic and animal welfare problems [6].…”
Section: Introductionmentioning
confidence: 99%